Intrinsic coagulation pathway-mediated thrombin generation in mouse whole blood - Konrath, Sandra; Mailer, Reiner K.; Beerens, Manu; Englert, Hanna; Frye, Maike; Kuta, Piotr; Preston, Roger J. S.; Maas, Coen; Butler, Lynn M.; Roest, Mark; de Laat, Bas; Renné, Thomas (Frontiers in Cardiovascular Medicine, 2022)
Calibrated Automated Thrombography (CAT) is a versatile and sensitive method for analyzing coagulation reactions culminating in thrombin generation (TG). Here, we present a CAT method for analyzing TG in murine whole blood by adapting the CAT assay used for measuring TG in human plasma. Artificial and physiologic factor XII (FXII) contact activators kaolin, ellagic acid and synthetic polyphosphate (polyP) stimulated TG in murine blood in a dose-dependent manner resulting in a gradual increase in endogenous thrombin potentials and peak thrombin, with shortened lag times and times to peak. The activated FXII inhibitor rHA-Infestin-4 interfered with TG triggered by kaolin, ellagic acid and polyP and TG was completely attenuated in blood of FXII-deficient (F12-/-) mice. Moreover, reconstitution of blood from F12-/- mice with human FXII restored impaired contact-stimulated TG. HEK293 cell-purified polyP also initiated FXII-driven TG in mouse blood and addition of the selective inhibitor PPX_12 ablated natural polyP-stimulated TG. In conclusion, the data provide a method for analysis of contact activation-mediated TG in murine whole blood. As the FXII-driven intrinsic pathway of coagulation has emerged as novel target for antithrombotic agents that are validated in mouse thrombosis and bleeding models, our novel assay could expedite therapeutic drug development.